Increasing Tourist Visits Through Ecotourism Elements, Electronic Word of Mouth and Destination Image - Yolanda, Dian Rani; Susdiani, Laela (Politeknik Negeri Padang, 2023)
This study aims to examine the effect of ecotourism elements, electronic word of mouth and destination image on visit decisions. This study is an explanatory research with quantitative methods. The object of this study is the Harau Valley Area, Lima Puluh Kota Regency in West Sumatra. The non-probability sampling method with purposive sampling was used to determine the sample for this research. The sample of this study were respondents aged more than 18 years who had visited and accessed information related to the Harau Valley tourist attraction through the website and various existing social media sites such as Facebook, Instagram, and others. This research utilizes primary data obtained through field research by distributing questionnaires directly to 170 visitors in the Harau Valley Tourism Area. Multiple linear regression were used as the test tools for this study. The data was processed using the SPSS program.The results show that there are significant influence between ecotourism elements, electronic word of mouth and destination image on visit decision.